URINARY NEOPTERINE LEVELS IN PATIENTS WITH MAJOR DEPRESSIVE DISORDER: ALTERATIONS AFTER TREATMENT WITH PAROXETINE AND COMPARISON WITH HEALTHY CONTROLS - Taymur, Ibrahim; Ozdel, Kadir; Ozen, Nurper Erberk; Gungor, Buket Belkiz; Atmaca, Murad (Medicinska Naklada, 2015)
Background: A close relationship has been shown between mood disorders and pteridine levels. The aim of this study was to examine alterations in the urine neopterine levels of patients with major depressive disorder (MDD) who responded to paroxetine during the initial treatment and to compare their levels to those of healthy controls. Subjects and methods: Sixteen patients with major depression and 19 healthy controls were enrolled in the study. In order to assess depression severity levels, the Beck Depression Inventory, the Beck Anxiety Inventory, and the State-Trait Anxiety Inventory were administered. Urinary neopterine values that were measured using high pressure liquid chromatography (HPLC) were compared using non-parametric tests for the MDD patients before and after treatment. Urine neopterine levels in MDD patients before and after treatment were compared to those of the healthy control group. Results: Urinary neopterine levels were recorded as follows: For the MDD group before treatment the mean level was 187.92 +/- 54.79 mu mol/creatinine. The same group under treatment at 4 to 8 weeks was at 188.53 +/- 4962 mu mol/creatinine, and the healthy control group showed 150.57 +/- 152.98 mu mol/creatinine levels. There was no statistically significant difference in the urinary neopterine levels among the MDD patients before and after treatment (p=0.938). When urine neopterine levels in MDD patients before and after treatment were compared to those of the healthy control group, levels in the MDD group were found to be significantly higher (p=0.004 and p=0.005, respectively). Conclusions: Findings from the current study suggest that despite treatment response, depression is related to higher levels of urine neopterine. Paroxetine treatment has no significant effect on urine levels of neopterine in MDD patients.
Keywords: neopterine; depression; MDD; immune system; paroxetine